The effectiveness of the Madrasati platform according to the Needham constructivist model in increasing achievement of second-year intermediate female students in the TIMSS tests (algebra field) and the teacher’s point of view - Alfifi, Mariam Farhan; Al-Sahli, Ghada Owaid Awad (Arab Journal for Sciences and Research Publishing, 2024)
The reports of the Education Evaluation Commission in the Kingdom of Saudi Arabia monitored the average performance of second-year intermediate students in the TIMSS international tests in the three consecutive years 2011, 2015, and 2019. The reports indicate a decline in the level of students’ performance and obtaining lagging positions, as the Kingdom ranked (37) Out of (39) participating countries in 2019, and as an investment in the efforts of the Ministry of Education in developing education, the current study sought to train female second-year intermediate students to develop thinking skills to solve problems simulating international test questions (TIMSS) (algebra field) using the Madrasati platform according to the Needham constructivist model. The study applied the mixed approach on a purposive sample of (20) students. They were tested with a pre-test, followed by a proposed educational program using Needham’s constructivist strategy through suggested cards in a sequence consistent with Needham’s model with its five stages, the training phase was followed by a post-test for the female sample students.The results of quantitative and descriptive data analysis showed positive impact of the training according to the proposed educational program, and effectiveness of the Madrasati platform according to the Needham constructivist model in increasing the achievement of second-year intermediate female students in the international tests TIMSS (algebra field).
Keywords: Nidham’s Model; algebra; Intermediate grade students; madrasati platform; mathematics’ teachers; TIMSS